“Impacto de la evaluación ex post en la carrera departamental SM-102, tramo: San José de Sisa-Aguan Blanca-San Pablo-Empalme PE-5N (DV. Bellavista), Provincias de El Dorado y Bellavista, Región San Martín” - Encomenderos Dávalos, Danny Oldy (2014)
This research raises aimed to evaluate the impact of investment Ex Post with the project intervention in rehabilitation and improvement of departmental road San José de Sisa - Bellavista. To achieve this purpose, we worked with a random sample of intentional type identified in 92 beneficiaries Area of Direct lnfluence of the project, between freight and passenger transport, Educational lnstitutions, Health lnstitutions, local authorities and boards of organizations Agricultura! Producers The main problem was: What has been the impact of the Ex Post lnvestment made in the rehabilitation and improvement of the Departmental Road SM - 102 Section: San José de Sisa-Agua Blanca-San Pablo-Empalme PE-5N (DV. Bellavista), Provinces El Dorado and Bellavista, San Martín Region. The solution is to evaluate the impacts guided by the objectives, comparing the situation before and after the intervention, determine to what extent were achieved the expected impacts and analyze what were the direct and indirect changes in the target population of the Area of Direct lnfluence the Project. Simple design Before and After evaluation was used to compare baseline of object goal against the final situation after the intervention through the project for calibration. To fulfill the objectives a semi structured survey questions considered in the dimensions related to indicators that the project was made in the logical framework was used. The analysis of information was supplemented. Thus he arrived at conclusions that the beneficiary population Direct lnfluence Area Project accused favorable impacts by reducing transportation costs and walkability, access to consumer markets and social services more smoothly.